2012
DOI: 10.1111/j.1545-5300.2012.01409.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Representations of Coparenting Among Unmarried First‐Time African American Mothers

Abstract: Results of semistructured interviews with 45 pregnant unmarried first-time African American mothers indicated a wide range of expectancies concerning the coparenting relationship they would develop with others once their baby arrived. Most common coparenting systems projected by respondents involved maternal grandmothers and/or the babies' fathers, though other caregivers were explicitly anticipated in a smaller number of cases. Multiperson coparenting systems were the norm, and only 2 of 45 respondents antici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…As such, instead of focusing on father involvement or lack of involvement in the coparenting role, this study aims to highlight the realities of the diverse coparenting alliances that evolve in many African American single‐mother families and the impact of these diverse alliances on youth externalizing problems (Burton & Hardaway, ; Carlson & Hognas, ; Gaskin‐Butler, Engert, Markievitz, Swenson, & McHale, ; McHale, Waller, & Pearson, ; Roy & Burton, ). Importantly, the coparenting literature does not specify that a romantic or marital relationship is inherent or even implied in the coparenting construct (McHale & Lindahl, ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, instead of focusing on father involvement or lack of involvement in the coparenting role, this study aims to highlight the realities of the diverse coparenting alliances that evolve in many African American single‐mother families and the impact of these diverse alliances on youth externalizing problems (Burton & Hardaway, ; Carlson & Hognas, ; Gaskin‐Butler, Engert, Markievitz, Swenson, & McHale, ; McHale, Waller, & Pearson, ; Roy & Burton, ). Importantly, the coparenting literature does not specify that a romantic or marital relationship is inherent or even implied in the coparenting construct (McHale & Lindahl, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to shifts in the broader society related to women's increased participation in the labor market and public policies and initiatives promoting “responsible fatherhood,” fathers are being encouraged to take more active roles in their children's affective growth and development (Lamb & Tamis‐Lemonda, ). Specifically, there is more interest in aspects of fatherhood such as the quantity and quality of time spent in caregiving activities, the impact of fathers' involvement on children's socialization, and their ability or willingness to effectively coparent with their children's mothers (Burton & Hardaway, ; Gaskin‐Butler, Engert, Markievitz, Swenson, & McHale, ; Marsiglio, Amato, Day, & Lamb, ; McHale & Waller, ). A by‐product of this increased interest in fatherhood and the roles of fathers is that the fatherhood literature has been significantly bolstered.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…28 In addition, Black and Nitz examined a population of urban, low-income, first-time adolescent mothers residing with the maternal grandmother of the infant and found that the coresiding grandmother appeared to facilitate more support for the adolescent role (e.g., mothers were more likely to remain in school), than for the maternal role; thus suggesting that the support of the maternal grandmother was primarily directed toward facilitating the mother's growth and development. 29 Similarly, literature specifically focused on black mothers of primarily term infants demonstrates that the opinion of the mother's mother is very important.…”
mentioning
confidence: 99%